A rare case of long subserosal paracolic subhepatic appendix - Ranga, Hansraj; Vidit, Vidit; Singh, Tarun; Sehrawat, Versha; Choudhary, Ruchi (International Surgery Journal, 2024)
Appendicitis is the most common surgical emergency worldwide with variable presentation and unusual positions of appendix. Subhepatic appendicitis is a rare presentation due to congenital malpositioning of the appendix under the liver rather than its typical location in right iliac fossa. This atypical location of appendix leads to recurrent episodes of appendicitis, delayed diagnosis and increased risk of complications. In this case report, A 17-year-young female presented to the emergency room with complaints of pain in right lower abdomen associated with vomiting and fever for 3 days, diagnosed with sub-acute appendicitis. She also had similar 3 episodes in past with complaints of pain in the abdomen for the last one year. She managed conservatively and with advice of a laparoscopic interval appendectomy. Intra-operatively, she was diagnosed with long subserosal paracolic subhepatic appendix. Through previous literature reviews and case analysis, this case report highlights the importance of the unusual position of the appendix and its surgical management. Clinicians should keep all anatomical variants in mind while diagnosing appendicitis for early recognition, prevention of recurrent episodes and complications associated with delayed treatment.